PEMANFAATAN LAHAN NON PRODUKTIF UNTUK TANAMAN OBAT KELUARGA DI DESA TELUK BAYUR, KABUPATEN BERAU - Heru Herlambang; Halimatus Sakdiyah; Aldifira Ruswana; Putra Pratama; Alayya Widya; Siti Nurhalimah; Andika; Ahmad Takwin; Agnes Langouran (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2022)
Land use by the community is an activity to make unproductive lands more valuable and beneficial to the community. Building a model plot for a family medicinal plant garden is useful for providing a source of traditional medicines and aesthetic value and fulfilling household needs. Activities for making a medicinal plant garden (TOGA) and counseling on how to make traditional medicine have been carried out in The Teluk Bayur Village, Berau Regency. The enthusiastic and participatory community made a family medicinal plant garden beside the village office. A total of 40 plants from 14 species of plants have been collected and planted with beautiful designs. The community also formed a TOGA park administrator in The Teluk Bayur sub-district, which aims to make the management of the TOGA park sustainable.